Implementation of Compensation for Defective Goods in Khiyar Cases at Roworejo Market, Indonesia - Adnan Daffa Syahdilla; Nurnazli; Ahmad Sukandi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2026)
Purpose – This study examines the implementation of compensation for defective goods in clothing transactions at Roworejo Market. Specifically, it focuses on the seller's liability for defective goods and evaluates its principles and consistency within Islamic economic law, particularly regarding the concept of khiyar. Method – This research employs a descriptive qualitative approach using field observations, interviews with clothing vendors at Roworejo Market, documentation, and literature review on Islamic economic law and khiyār principles. Result – The study finds that unclear return and take-home policies for clothing goods often trigger disputes over defective products and weaken the seller’s position in transactions. From the perspective of Islamic economic law, such practices contain elements of gharar and ḍarar, indicating that the implementation of khiyār has not been carried out optimally. In addition, the absence of standardized agreements among sellers has resulted in weak legal certainty and inconsistent compensation practices. Implication – This study could be valuable to traders, customers and local authorities to develop a fairer and more transparent market transaction process based on the Islamic economic law. The research underlines the necessity to standardize the agreements and compensation procedures according to the principles of khiyār to limit the occurrence of disputes in traditional market transactions. Compensation systems and khiyār-based arrangements can help support honesty and social cohesion in traditional market groups.